Reconfigurable Adaptive Multiple Transform Hardware Solutions for Versatile Video Coding - Carlo Sau; Dario Ligas; Tiziana Fanni; Luigi Raffo; Francesca Palumbo (IEEE Access, 2019)
Computer aided design is nowadays a must to quickly provide optimized circuits, to cope with stringent time to market constraints, and to be able to guarantee colliding constrained requirements. Design automation is exploited, whenever possible, to speed up the design process and relieve the developers from error prone customization, optimization and tuning phases. In this work we study the possibility of adopting automated algorithms for the optimization of reconfigurable multiple constant multiplication circuits. In particular, an exploration of novel reconfigurable Adaptive Multiple Transform circuital solutions adoptable in video coding applications has been conducted. These solutions have also been compared with the unique similar work at the state of the art, revealing to be beneficial under certain constraints. Moreover, the proposed approach has been generalized with some guidelines helpful to designers facing similar problems.